Donor Portraits in the Sculptural Decoration of the Early Zakarid Era Churches in Ani - Loshkareva, Ekaterina A. (Actual Problems of Theory and History of Art, 2023)
The article is devoted to the analysis of the donor sculptural portraits composition of St. Gregory (Bakghtagek’s) and Inner Fortress (Aghjkaberd) churches in Ani. Both of these fragmentary sculptures were discovered during the archaeological campaign in Ani curated by the Imperial Archaeological Commission and were subsequently lost. It turned out the photographs of these fragments have survived, but researchers did not report on these photographs for many years. These images were discovered and attributed by the author of this article. The critical analysis of the obtained images allowed to recreate partially the original forms of donor sculptural portraits in both of these churches. Finally, an assumption was made about the location of this composition in the church building based on architectural features of the Ani school during the Early Zakarid era and the existing tradition of Armenian donor sculptural portraits.The study was supported by the grant of the Russian Science Foundation, project no. 22-18-00354, in the National Research Moscow State University of Civil Engineering (NRU MGSU).
Keywords: Ani; Marr; Bakhtagek’s church; Aghjkaberd; Medieval sculpture; Armenian architecture; church model; archaeological campaign; Mkhargrdzeli